Application of an iPSC‐Derived Organoid Model for Localized Scleroderma Therapy. Issue 16 (22nd March 2022) - Ma, Jie; Li, Wei; Cao, Ruiyuan; Gao, Dunqin; Zhang, Qiyu; Li, Xiao; Li, Biyou; Lv, Luye; Li, Mansheng; Jiang, Junyi; Wang, Yujie; Li, Jun; et al.
Abstract: Localized scleroderma (LoS) is a rare chronic disease with extensive tissue fibrosis, inflammatory infiltration, microvascular alterations, and epidermal appendage lesions. However, a deeper understanding of the pathogenesis and treatment strategies of LoS is currently limited. In the present work, a proteome map of LoS skin is established, and the pathological features of LoS skin are characterized. Most importantly, a human‐induced pluripotent stem cell‐derived epithelial and mesenchymal (EM) organoids model in a 3D culture system for LoS therapy is established. According to the findings, the application of EM organoids on scleroderma skin can significantly reduce the degree of skin fibrosis. In particular, EM organoids enhance the activity of epidermal stem cells in the LoS skin and promotes the regeneration of sweat glands and blood vessels. These results highlight the potential application of organoids for promoting the recovery of scleroderma associated phenotypes and skin‐associated functions. Furthermore, it can provide a new therapeutic alternative for patients suffering from disfigurement and skin function defects caused by LoS. Abstract : A proteome map of localized scleroderma (LoS) skin is established. A human‐induced pluripotent stem cell‐derived epithelial and mesenchymal organoids model is constructed and applied for LoS therapy. The study results highlight the potential application of organoids for promoting the recovery of scleroderma associated phenotypes and skin‐associated functions.